Asymmetric dimethylarginine and NO metabolites in patients with acute and chronic coronary heart disease - A. S. Galyavich (Кардиоваскулярная терапия и профилактика, 2009)
Aim.То study the levels of asymmetric dimethylarginine (ADMA) and NO metabolites in patients with ST elevation acute coronary syndrome (ACS-ST), as well as in patients with stable effort angina (SEA). Material and methods. The study involved 35 patients: 20 with ACS-ST (mean age 57,4±9,2 years) and 15 with SEA (mean age 57±7,1 years). All participants underwent standard examination and measurement of ADMA and NO metabolite (nitrites, nitrates) concentration in venous blood at admission and after 2 weeks of treatment, with the final examination at 12 months.Results. At baseline, ACS-ST patients demonstrated significant increase in ADMA and reduction in NO metabolites. After 2 weeks of treatment, no significant difference in NO metabolite levels was observed between two groups. Non-significant difference in pre- and post-treatment ADMA concentration was registered in ACS-ST patients, but this difference reached statistical significance in the subgroup of ACS-ST participants without arterial hypertension. The patients who suffered a recurrent fatal myocardial infarction within the next 12 months, demonstrated higher ADMA concentrations than all ACS individuals.Conclusion. ACS-ST patients had increased ADMA levels and reduced NO metabolite concentrations. In treated ACS-ST patients, NO metabolite levels increased.